MANAJEMEN KEGIATAN BUDIDAYA RUMPUT LAUT EUCHEUMA COTTONII DI DESA NURUWE KABUPATEN SERAM BAGIAN BARAT - Matakupan, Jolen; Louhenapessy, Danniel G.; Sahetapy, Jacqueline M. F; Pattipeilohy, Christian. E. (Jurnal Abdi Insani, 2024)
Seaweed is one of the marine biological resources whose production is sustainable and environmentally friendly. Eucheuma cottonii is a seaweed that has high economic value as a carrageenan producer. West Seram Regency is one of the production centers of seaweed development in Maluku Province with a growing production value from 2005 which was 50.5 tonnes until 2009 production reached 681.8 tonnes, an area of use of 688 ha. One of the villages in West Seram Regency that plays a role in the contribution of seaweed cultivation and seaweed exports nationally is Nuruwe Village with the type of seaweed cultivated is E.cottonii. This activity aims to find out how the management of E. cottonii seaweed cultivation activities and what are the factors that determine the success of the cultivation group in Nuruwe Village, West Seram Regency. This activity was carried out in September 2023. The method of activities was carried out in the form of interviews with the head of the seaweed cultivation business group. The results of this activity showed that there was a reduction in the number of seaweed cultivation business groups from fourteen groups to four groups in 2021. The seaweed cultivation business group that still survives is the "Titapo" group. The cultivation method used is the floating raft method. The highest production peak of E. cottonii seaweed cultivation in 2009 (96 tonnes) was due to the attack of ice-ice disease and epiphytes as well as non-continuous seedlings. This activity concludes that seaweed diseases and seed availability are among the limiting factors that need attention to help increase seaweed production in Nuruwe village, West Seram district.